South Korean Government’s Role in Public Diplomacy: A Case Study of the Korean Wave Boom - Sofia Trisni; Putiviola Elian Nasir; Rika Isnarti; Ferdian - (Department of International Relations, Universitas Andalas, 2019)
Korean wave has became a current booming popular culture; reaching all continents of the world. This phenomenon is the result of cooperation from various actors, namely state and non-state actors. This paper aims to determine the role of the South Korean government in the accomplishments achieved by the Korean wave to date, by studying the literature that focuses on the Korean wave success. This paper concludes that the South Korean government acts as a stimulator, regulator and facility provider for the cultural industry to develop. While the success of the Korean wave in penetrating the world market is the result of the formulation of strategies and promotions conducted by non-state actors involved in the process of producing the Korean wave.